Being the body in question: young people's accounts of everyday ableism, visibility and disability. Issue 1 (2nd January 2020) - Calder-Dawe, Octavia; Witten, Karen; Carroll, Penelope
Abstract: The perception of impairments often relies on dominant, ableist presumptions about what disability 'looks like'. This article builds from in-depth research with 35 young people who are Deaf or blind or have vision, hearing or mobility impairments and their parents, all of whom navigated ableist interactional dynamics in one form or another. In conversation with scholarship across disability studies, sociology and social psychology, this article explores how the perception of differences and disabilities influences everyday interactions. Our analysis teases out a series of relationships between the (non-)perception of participants' impairments and the form and frequency of ableist intrusions they experienced. We focus, in particular, on the medicalised, diagnostic tenor of everyday encounters, wherein participants are routinely stared at, questioned, assisted and challenged by strangers. Our analysis points to the medicalised, ocularcentric nature of everyday ableism, demonstrating how these encounters function to sustain the interactional and social privileges of able-bodied people.